2016
DOI: 10.18632/oncotarget.8088
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 gene expression interacts with environmental enrichment to impact lifespan and behavior

Abstract: Aging produces cellular, molecular, and behavioral changes affecting many areas of the brain. The dopamine (DA) system is known to be vulnerable to the effects of aging, which regulate behavioral functions such as locomotor activity, body weight, and reward and cognition. In particular, age-related DA D2 receptor (D2R) changes have been of particular interest given its relationship with addiction and other rewarding behavioral properties. Male and female wild-type (Drd2 +/+), heterozygous (Drd2 +/−) and knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 87 publications
2
22
0
1
Order By: Relevance
“…We next decided to investigate whether the hh mutant flies exhibit any survival or behavioral deficits, because defects in the dopaminergic neuron network have been demonstrated to have a detrimental effect upon lifespan and locomotor activity in both mammals and invertebrates (Thanos et al, 2016;Liao et al, 2017;Feany and Bender, 2000). Strikingly, we found that both female and male adult hh ts flies shifted to 29 C exhibit a drastically shortened lifespan (80%-85% decrease in the median lifespan when compared to control flies) (Figures 2A and S3C; Table S2).…”
Section: Adult Expression Of Hh Is Necessary For Correct Lifespan Detmentioning
confidence: 99%
“…We next decided to investigate whether the hh mutant flies exhibit any survival or behavioral deficits, because defects in the dopaminergic neuron network have been demonstrated to have a detrimental effect upon lifespan and locomotor activity in both mammals and invertebrates (Thanos et al, 2016;Liao et al, 2017;Feany and Bender, 2000). Strikingly, we found that both female and male adult hh ts flies shifted to 29 C exhibit a drastically shortened lifespan (80%-85% decrease in the median lifespan when compared to control flies) (Figures 2A and S3C; Table S2).…”
Section: Adult Expression Of Hh Is Necessary For Correct Lifespan Detmentioning
confidence: 99%
“…D2R in the striatum has been associated with the regulation of motivated, appetitive behavior, including reinforcement learning and behavioral flexibility. D2R has also been implicated in generalized behavioral activation (Tataranni et al, 2001 ; Kravitz et al, 2010 ; Klinker et al, 2013 ; Beeler et al, 2016 ; Friend et al, 2016 ; Lemos et al, 2016 ; Thanos et al, 2016 ). Each could potentially explain the other; that is, blocking D2R could reduce motivation, effectively reducing activity or, conversely, a generalized restriction on activity and energy expenditure could diminish apparent motivation.…”
Section: Controlling the Energy Budget: Striatum As Substrate Implemementioning
confidence: 99%
“…The traditionally used therapeutic agents have failed to address the reduced connectivity patterns now seen in many addictions and have had limited success in relapse prevention and effective recovery from psychoactive substance abuse [4,54]. This concept would enable genetic testing and precise treatment of genetic and epigenetic deficits with formulations of KB220 [55,56]. Recovery and good health would be the goal of this SMART, holistic program design, based on this extensive research in a diverse but stable population [57].…”
Section: Resultsmentioning
confidence: 99%